Shoulder strength, flexibility and injury profiles of high school water polo players - Devine, Gareth (My University, 2014)
The aim of this research was to determine the flexibility and strength of the internal and external rotators of the shoulder and injuries that occur in the shoulder in male high school water polo players. A cross sectional study was done with a convenient sample of 28 male high school water polo players. Flexibility was assessed using Myrin inclinometer and strength was assessed using the Biodex System 3 isokinetic dynamometer. The tests were done to assess the player’s internal and external rotators of the shoulder. The participants were also questioned using a questionnaire to see time spent playing water polo, injuries sustained and type of injuries. The results showed increased external rotation flexibility and strength in the shoulder compared to internal rotation flexibility and strength. A strong correlation between the internal and external rotators of the same shoulder was also seen in the water polo players when looking at flexibility and strength. Even though the evidence showed that the water polo player would have adaptations in the shoulder due to the movements performed, there was very little correlation between shoulder external rotation flexibility and strength. With the different movements of the water polo player’s shoulder it is shown how the different vigorous movements of water polo alter biomechanics to help in their movements during water polo. Future studies need to focus on the different adaptations during water polo and whether these adaptations cause injury or better performance.